Hypertension Control in Patients Attending Outpatient Department: A Hospital Based Study from Lumbini Province Nepal - Gautam, Samir; Dhungel, Sachin; KC, Bishal; Khan, Majhar; Shakya, Abhishesh; Panjiyar, Rajesh (Journal of National Heart and Lung Society Nepal, 2023)
Background: Systemic hypertension is major public health problem. It is easy to diagnose and initiate treatment. But still it remains under detected, undertreated and less well controlled throughout the world. We wanted to know control of hypertension in patients attending outpatient department in a cardiac center. Methods: This is a cross-sectional observational study conducted at Gautam Buddha Community Heart Hospital. One hundred newly detected hypertensive patients attending outpatient department were evaluated in this study. Results: Distribution of patients was males 56% and females 44%. Most patients (55%) were in the age group 45 to 65 years. Headache (42%) and dizziness (39%) were common symptoms at presentation. Majority of hypertensive pa-tients had blood pressure range 140 to 160 SBP (49%) and 90 to 100 DBP (56%). Hypertension control target reached in 69% for SBP and 90% for DBP at one month. Target blood pressure was present in 82% for SBP and 84% for DBP at three months follow up. Conclusion: Hypertension management in short term appears promising but long term control is more important to prevent complications. So long term fol-low up study or national registry database is important.